Makna Lirik Nyanyian Andung Dalam Upacara Kematian Sarimatua Pada Masyarakat Batak Toba di Samosir - Daniel Yosmar Heyman Manalu (Institut Seni Indonesia Yogyakarta, 2018)
This study discusses the function and meaning of lyric singing in the ceremony of sarimatua death in Batak Toba society in Samosir. In general, there are problems identified in this study. The main problem is hata andung is rarely used by the Toba Batak community. Batak Toba community more often use the Batak Toba language because not many people Toba Batak who understand about the meaning of andung the truth. For that language andung should be used with hata andung no longer used, so it does not have the value of the tradition attached to the Batak Toba community in Samosir. study conducted during the period of four months, from the beginning of February 2017 to May 2017.To discuss the problem then used the theory of Abdul Chaer in assessing the function and meaning, cultural values contained in andung sarimatua Ompu Juan Boru. The results of this study resulted in some conclusions such as singing andung lacks existence in the Batak community because, the speakers at the ceremony andung Toba batak community dead at the present time is very difficult to find. This andung tradition is considered no longer suitable for today. Some of the factors that result in shifts and changes in the current andung sarimatua traditions are religion, language, and the use of musical instruments.The function of the andung tradition at present in the Toba Batak community death ceremony include: the function of expression of sadness and the closeness of relationships and respect for the deceased family. The meaning contained in andung sarimatua reveals all the feelings and tells the contents of his heart to his deceased mother, tells many things, the longing of sipangandung to uncle and grandfather who have long died also participated expressed and send greetings to them, and expect her mother still can protect his descendants. Cultural values contained in the tradition andung in the ceremony of death sarimatua Batak Toba community today is the value of hasangapon, hagabeon, and hamoraon.